(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background : The prime imaging modality available for imaging the posterior fossa are CT and MRI. CT is non-invasive, provides 3-D cross sectional anatomy of brain, which can be reformatted in multiple planes. CT provides more detail about the nature of calcification. The posterior fossa lesions can be broadly classified into 1) Mass lesions 2) Inflammatory lesions 3) Traumatic lesions 4) Vascular lesions 5) Congenital malformations. Objective is to evaluate the computed tomography features of various types of lesions in the posterior fossa, their appearances and to determine the age and sex distribution. Materials and Methods: This was a prospective study carried out on 60 patients, age range was 0-80 years, who were referred to the Department of Radio-Diagnosis for CT at Rohilkhand Medical College and Hospital for a period of one year from November 2018 to October 2019 using 16 slice GE Brightspeed Elite third generation CT machine. Results & Conclusion: CT was highly accurate and efficient in diagnosing various posterior fossa lesions. It has an upper hand over MRI in characterization of bony changes and calcification.